TREATMENT OF HARVESTED RAINWATER USING BIOSAND FILTRATION SYSTEM WITH UV DISINFECTION - Jong, Maliani (Universiti Teknologi PETRONAS, 2018)
According to World Health Organisation (2006), around 884 million people worldwide were inaccessible to safe drinking water due to having water quality issues which are mainly caused by the presence of microbial pathogens in the water. The objective of this paper is to focus on assessing water quality of harvested rainwater from first flush system and developing water treatment by using Biosand Filtration (BSF) system with UV Disinfection. BSF system together with UV Disinfection are two of the technologies that are practically used in many developed countries to help overcoming the water quality issues. By applying this set of water treatment, this research paper explains about the impact of water filtration and disinfection towards water quality. In other words, it includes the information sources on how water treatment can assist water quality. To achieve the objectives of this paper, fabrications of BSF system with UV Disinfection are done before proceeding to harvested rainwater collection and water treatments using fabricated BSF system with UV Disinfection followed by water quality testing, data collection, data analysis, and data record. The water quality parameters used in this research consists of three properties such as physical, chemical, and biological factors.